2018
DOI: 10.3389/fnbeh.2018.00256
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Plasticity of Audiovisual Perception: Rapid Recalibration of Temporal Sensitivity but Not Perceptual Binding Following Adult-Onset Hearing Loss

Abstract: The ability to accurately integrate or bind stimuli from more than one sensory modality is highly dependent on the features of the stimuli, such as their intensity and relative timing. Previous studies have demonstrated that the ability to perceptually bind stimuli is impaired in various clinical conditions such as autism, dyslexia, schizophrenia, as well as aging. However, it remains unknown if adult-onset hearing loss, separate from aging, influences audiovisual temporal acuity. In the present study, rats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…Consistent with human testing, a psychophysical profile was generated for each rat by plotting straight lines between each of the neighboring SOAs and the associated slope and intercept values were calculated [26]. Using these values, the point of subjective simultaneity (PSS) and just noticeable difference (JND) was calculated for each of the test sessions [24, 25, 27]. For each of the SJ test sessions, performance for all 5 SOAs was measured as the proportion of trials in which the rat perceived the stimuli as synchronous (i.e., responded to the left feeder trough, Figure 1(a)).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with human testing, a psychophysical profile was generated for each rat by plotting straight lines between each of the neighboring SOAs and the associated slope and intercept values were calculated [26]. Using these values, the point of subjective simultaneity (PSS) and just noticeable difference (JND) was calculated for each of the test sessions [24, 25, 27]. For each of the SJ test sessions, performance for all 5 SOAs was measured as the proportion of trials in which the rat perceived the stimuli as synchronous (i.e., responded to the left feeder trough, Figure 1(a)).…”
Section: Methodsmentioning
confidence: 99%
“…Of the few reports available, however, it appears that audiovisual synchrony perception is largely preserved in hearing-impaired subjects [2123], provided that potential confounding factors, such as aging, are addressed. Moreover, we recently reported that adult rats with a moderate hearing loss experienced a rapid recalibration of their ability to accurately judge the order of audiovisual stimuli, with temporal perception being restored two weeks following the loud noise exposure [24]. This inconsistency between the extent of crossmodal plasticity reported previously and the apparent lack of behavioral consequences raises an important question: how is the brain able to maintain (or re-establish) temporally precise audiovisual integration and perception in the presence of extensive sensory reorganization in the cortical regions thought to subserve such behavioral tasks?…”
Section: Introductionmentioning
confidence: 99%
“…SJ and TOJ tasks : [Schormans & Allman, 2018; Schormans, Scott, et al, 2017; Schormans, Typlt, & Allman, 2017]…”
Section: The Neurobiology Of Multisensory Integrationmentioning
confidence: 99%
“…In the awake, behaving rat, Hirokawa and colleagues used pharmacology to transiently disrupt and identify a border region between the primary visual and auditory cortices, known as the lateral part of V2 or V2L, that is critical for audiovisual processing in rats [Hirokawa et al, 2008]. Allman and colleagues recently investigated the role of V2L in multisensory temporal processing [Schormans & Allman, 2018; Schormans, Scott, et al, 2017]. Remarkably, rats are capable of performing classic psychophysical simultaneity judgment (SJ) and temporal order judgment (TOJ) tasks [Schormans, Scott, et al, 2017], generating TBWs that appear to be similar to those found in the human population [Wallace & Stevenson, 2014].…”
Section: Multisensory Studies In Ratsmentioning
confidence: 99%
See 1 more Smart Citation